DECLASSIFIED DIALOGUES Music and archive-body in the construction of an unfinished knowledge (firststeps) (Orfeu, 2020)
The present study is part of the growing recognition of the importance of the archive-body for the understanding of the more specific performance practices when applied to Music. This proposal for reflection has been taking shape due to the expansion of a structural classification process present in the daily life of our societies and which has become a reason for other possible realities. In this context, we formulate critical thinking under this logic while highlighting certain questions that are important for artists and that are of interest to musicologists. The main objective is to allow the application of the concept of body-file in the field of musical studies. Starting from a set of approaches, the article, on the one hand, presentsand develops as ways in which it is possible, from the disqualification, to carry out this application. From another perspective, this work can analyze how the musicians highlighted in this process face as their performative experiences.
Keywords: Music; Archive-Body; Classification/Declassification; Construction of Knowledge